The emerging trends in antimicrobial susceptibility pattern of Pseudomonas species: A hospital-based cross-sectional study at a tertiary care hospital of South Bihar. - Barnawal, Ravindra Kumar; Kumar, Rakesh; Kumar, Ashwini; Srivastava, Ranjan Kumar (Student’s Journal of Health Research Africa, 2025)
Background Infections caused by Pseudomonas spp. are becoming more common in immunocompromised patients, particularly in hospital settings. The most well-known member of this family is Pseudomonas aeruginosa, a serious pathogen. To develop antibiograms, this study examined the distribution and susceptibility patterns of Pseudomonas species isolated from various specimens as part of a surveillance program. Objectives: This study aimed to determine the prevalence and analyze the antibiogram of Pseudomonas species at a tertiary care hospital in South Bihar. Methods A hospital-based, retrospective, cross-sectional study was conducted at a tertiary care hospital in South Bihar from February 2024 to January 2025. A total of 68 isolates of Pseudomonas species were isolated from 1862 various clinical specimens. For the isolation of the organisms, Blood Agar and MacConkey Agar plates were used. The oxidase test, catalase test, and gram staining were used to characterize phenotypes. The Clinical and Laboratory Standards Institute (CLSI), M100, 2024 recommendations were followed during the antibiotic susceptibility testing of anti-pseudomonal medications. Results Among the 68 isolates of Pseudomonas species that were isolated, the study found that pus was the most common specimen (46.8%), followed by urine specimens (18.75%). All the isolates were found sensitive to Colistin (100%), whereas Imipenem (76.6%) and Piperacillin-tazobactam (69.5%) were found sensitive in the majority of the isolates, followed by Amikacin (61.3%). Less than half of the isolates were found sensitive to Ciprofloxacin, Levofloxacin, and Gentamycin. Aztreonam had the lowest sensitivity (15%). Conclusions The study reveals a rising trend of multidrug resistance among Pseudomonas species, with limited susceptibility to commonly used antibiotics. Recommendation Regular antimicrobial surveillance and strict antibiotic stewardship programs are recommended to effectively manage and control multidrug-resistant Pseudomonas infections.